Age-specific maternal effects interact with larval food supply to modulate life history in Coleomegilla maculata - Vargas, German; Michaud, J. P.; Nechols, James R.; Moreno, Carlos A. (My University, 2014)
1. Maternal effects can modify progeny phenotypes to improve survival under variable conditions and may also interact with environment. 2. Four cohorts of C. maculata larvae were reared from four different points in their mothers' reproductive lives (1st, 12th, 24th and 36th oviposition days) and divided into two treatments for rearing; 30 min daily access to eggs of Ephestia kuehniella or ad libitum. 3. Progeny survival was lower on restricted food but increased over the first 12 oviposition days in both treatments, suggesting mothers did not conform to the theoretical norm, i.e., produce their 'best' progeny first. 4. Larval development was delayed on the restricted diet, but there was no effect of oviposition day on total developmental time, although pupation was faster in the final cohort than in the first. 5. The restricted diet amplified a developmental polymorphism evident in both treatments, increasing the percentage of larvae that added or subtracted an instar. The results suggest that mothers employ a mixed strategy and produce subsets of progeny that alternatively adopt an 'optimistic' or 'pessimistic' strategy when facing food limitation; undergo an additional instar to take advantage of any late improvement in the food supply, or forgo an instar and pupate at a small size. 6. A larger percentage of later cohorts pupated after only three instars in both treatments, suggesting that more later hatching progeny are maternally programmed for pessimism, as would be adaptive for larvae exploiting aphid populations in decline.
Citation: Vargas, G., Michaud, J. P., Nechols, J. R., & Moreno, C. A. (2014). Age-specific maternal effects interact with larval food supply to modulate life history in Coleomegilla maculate. Retrieved from http://krex.ksu.edu
Keywords: Developmental polymorphism; Egg size; Fecundity; Food limitation; Reproduction